The lunar cycle and inpatient sedation usage in a psychiatric setting - Mohamed, Faeeza (My University, 2019)
Introduction: This study aimed to investigate whether an association exists between the lunar cycle and the amount of sedation required by an inpatient psychiatric population. Methods: The study was a retrospective record review of psychiatric inpatient sedation usage at Chris Hani Baragwanath Academic Hospital, in Johannesburg, over 18 months. For each day in this period, data of the total amount of intramuscular sedation, the number of intramuscular injections administered and data of bed occupancy were collected and correlated with the days of the lunar cycle. Results: Outcomes included the amount (mg) of sedative administered and the number of intramuscular injections (per sedative and total) per bed occupied. There was no significant effect of any day of the lunar cycle on the amount of sedation dispensed or the number of intramuscular injections administered. Conclusion: Inpatient psychiatric illness severity, as measured by intramuscular sedation administered, is not exacerbated by the lunar cycle.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Medicine in the branch of Psychiatry Johannesburg, 2019
Keywords: Mental illness; Psychiatric nursing